The Effect of Infant Massage on Appetite in Infants Aged 6-12 Months - Annisa Fitri Basuki; Finta Isti Kundarti; Eny Sendra; Indah Rahmaningtyas (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Appetite is an important factor influencing infant growth and development. Infant massage has been reported as a complementary intervention that may improve feeding behavior and appetite in infants. This study aimed to determine the effect of infant massage on appetite among infants aged 6–12 months. This study employed a quasi-experimental pretest–posttest control group design. Forty infants were recruited through purposive sampling and divided into intervention (n=20), control (n=20) groups. The study was conducted in the working areas of the Sukorame Public Health Centres and the South Region Public Health Centre of Kediri City, from May 18 to June 18, 2025. The intervention group received infant massage twice weekly for four weeks, while the control group received standard care. Appetite was assessed using the Child Eating Behaviour Questionnaire (CEBQ). Data were analyzed using appropriate non-parametric statistical tests with a significance level of p<0.05. Appetite scores increased significantly in the intervention group from 94.6 to 97.6 (p=0.004), whereas no significant change was observed in the control group (p=0.336). Infant massage administered twice weekly for four weeks significantly improved appetite among infants aged 6–12 months and may be considered a safe complementary intervention to support infant feeding and growth.